2016
DOI: 10.1007/s00127-016-1188-5
|View full text |Cite
|
Sign up to set email alerts
|

Examining the need profiles of patients with multiple emergency department visits for mental health reasons: a cross-sectional study

Abstract: The repeat ED user group within case management may have distinct need profiles that require different treatment responses. Moreover, clinical needs rather than psychosocial needs have the greatest relationship with repeat psychiatric ED utilization. These unmet needs suggest areas for future interventions aimed at reducing the use of ED services for mental health reasons and improving care for patients who repeatedly present at the ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Class 3, which included individuals with moderate emergency department use, also differed from class 2 in terms of all predisposing and enabling factors, and several needs factors (drug use disorders, depression, schizophrenia and bipolar disorder). Regarding predisposing factors, individuals from class 3 showed several characteristics negatively associated with frequent emergency department use, such as female gender, 18 , 29 , 30 younger and middle age 34 36 and economic advantage. 22 , 29 Moreover, in terms of needs, class 3 individuals were mainly affected by common MDs (depression, anxiety), but relatively less affected by serious MDs or SUDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Class 3, which included individuals with moderate emergency department use, also differed from class 2 in terms of all predisposing and enabling factors, and several needs factors (drug use disorders, depression, schizophrenia and bipolar disorder). Regarding predisposing factors, individuals from class 3 showed several characteristics negatively associated with frequent emergency department use, such as female gender, 18 , 29 , 30 younger and middle age 34 36 and economic advantage. 22 , 29 Moreover, in terms of needs, class 3 individuals were mainly affected by common MDs (depression, anxiety), but relatively less affected by serious MDs or SUDs.…”
Section: Discussionmentioning
confidence: 99%
“…22,[30][31][32] Regarding predisposing factors, an association was found between higher frequency of emergency department use and male gender, 18,29,30 whereas the association between emergency department use and age categories was not consistent. 29,[33][34][35][36][37] Some studies have found that individuals with frequent emergency department use were more likely to have low incomes 29,38 and to be unemployed. 26,38 One study assessing hospital service use among people with SUDs found an association between emergency department use and lower levels of education.…”
mentioning
confidence: 99%
“…On the other hand, more flexible office hours could help diminish the need for ER service use. Many of the psychosocial reasons for seeking help at the ER are non-urgent (22), which is reflected in this study e.g. by the lack of emergency referrals to psychiatric inpatient care in the context of these visits.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, more flexible office hours could help diminish the need for ER service use. Many of the psychosocial reasons for seeking help at the ER are non-urgent, such as reasons related to insufficient housing or financial difficulties (22), which is reflected in this study e.g. by the lack of emergency referrals to psychiatric inpatient care.…”
Section: Discussionmentioning
confidence: 93%